Sosialisasi dan Pelatihan Pembuatan Minuman Rempah Instan Sehat Berbasis Tanaman Pekarangan di Desa Mundurejo Kecamatan Umbulsari Kabupaten Jember - Nidya Shara Mahardika; Andi Eko Wiyono; Jani Januar; Retha Talia Shasabilah; Rifqoh Anggarani Mulyana (Jurnal Pengabdian Masyarakat Formosa, 2022)
The community in Mundurejo village, Umbulsari sub-district, which is an area where there are many natural resources that are not utilized optimally in the form of spice plants that can be used as basic ingredients for making drinks that are useful for increasing body immunity. These spice plants contain curcuminoid compounds that function as immunostimulators in boosting the immune system. In addition, spices such as ginger, temulawak, turmeric, and lemongrass contain high enough antioxidants so that they can ward off free radicals in our bodies. This service activity is also carried out in order to provide education and training to the community regarding the processing of spice plants. The purpose of this service is to provide information about processing spices into traditional drinks that can increase body immunity. Devotion is done by providing an explanation of the stages of the manufacturing process, then followed by direct practice. The results of this community service are expected to increase knowledge and in processing spices, especially for recitation mothers and PKK mothers in Mundurejo Village, Umbulsari District. The results of this service are expected to be applied in industry, be it a household scale industry so that it can increase the selling or economic value of spice plants in the village of Mundurejo, Umbulsari District. This service program is carried out by introducing how to make instant spice drinks.